Ultrasound Diagnosed Rare Partial Nephrectomy Complication - Ettorre, Almut; Alejandre-Lafont, Enrique; Syed, Faeq Husain; Most, Astrid; Hamm, Christian W.; Bauer, Pascal (International Journal of Angiology, 2019)
Renal artery pseudoaneurysm (RAP) is a serious complication that can lead to severe hematuria, blood loss, and life-threatening hemorrhagic shock. A pseudoaneurysm is defined as an arterial wall deficiency that results in the accumulation of oxygenated blood in the nearby extraluminal region. Partial nephrectomy, a parenchymal sparing method, carries a lower risk of postoperative development of chronic kidney disease than total nephrectomy but a higher risk of iatrogenic vascular lesions such as RAP or arteriovenous fistulas. Pseudoaneursyms may develop secondary to arterial transection during tumor resection or due to arterial puncture during suture ligation of the resection bed. Emergency transarterial embolization is an effective treatment modality for patients with hemodynamic instability that does not lead to significant worsening of renal function. The recent literature reports an incidence of 2.7 to 21.7% of RAP or arteriovenous fistulas after partial nephrectomy. We report a case of severe bleeding with massive hematuria due to RAP, which was detected with duplex sonography.
Keywords: partial nephrectomy; renal artery pseudoaneurysm; duplex sonography; “to-and-fro” waveform; acute renal injury; coiling; postoperative complications